Finite element performance with different mesh size of retaining walls - Rohaya Alias; Siti Jahara Matlan; Anuar Kasa (IAEME Publication, 2020)
Finite element analysis is one of the efficient technique to support modern engineering practice. In the finite element analysis, mesh size assumes a significant role as it can determine the quality of the finite element analysis results. This paper investigates the influence of mesh size on finite element performances of concrete cantilever retaining walls. The finite element analysis of the concrete cantilever retaining walls was made using GeoStudio software consisting of SIGMA/W and SLOPE/W. Three mesh sizes are used to compare the accuracy of the model analysis, which is fine, medium and coarse size. The results of finite element analysis were compared with the results of field monitoring in order to validate the model. The finite element analysis results show the influence of the mesh size did not make a significant difference. It was discovered that the finite element models with fine mesh gave more close results when contrasted with field monitoring results. The results of finite element analysis and field monitoring were in good agreement.